The house of broken bricks : a novel - Williams, Fiona, 1975- (Henry Holt and Company, 2024)
"Set in a West Country farming village, The House of Broken Bricks lays bare the complexities of day-to-day life for a mixed-race family. Jess is a Londoner whose relationship with Richard transports her from a Jamaican diaspora in a city where she easily blends in into a creaking house on a floodplain where predatory birds hover over fields, eels coil in the river mud, buses run twice a day, neighbors barter honey for cider and no one looks like her. While Jess and Richard settle into the village rhythm, the dramatic arrival of their twin sons recasts the family dynamic, stirring up complicated feelings and questions of belonging. Full of surprises, deeply attuned to the rhythms of language and nature, this lyrical novel with a magical realist strand captures the pain and beauty of life and death as well as the transformational power of changing seasons"--